Parents\' lived experience of parenting challenges after divorce: A phenomenological study - Roya Hamidi; Sedigheh Ahmadi; Hassan Heydari (مجله علوم روانشناختی)
Background: Parenting is one of the most challenging tasks for parents post-divorce, which affects the mental health of children. However, few researchers have investigated parents' lived experiences of parenting post-divorce with a phenomenological approach, based on the impact of parents' ignorance and ineffective strategies of parents. Aims: The present study aimed to understand the parents' lived experience of the challenges of Parenting post divorce. Methods: This study employed a qualitative research approach, specifically utilizing the descriptive phenomenology method. The target population for this investigation comprised parents who underwent post-divorce parenting experiences in 2022. A total of 16 individuals actively engaged in parenting following divorce were selected as research participants. These participants were recruited through purposeful sampling, ensuring maximum diversity, and were drawn from individuals referred to Family Court Complex 1 in Tehran. The data collection method employed semi-structured interviews to glean insights from the participants. Subsequently, data analysis was conducted using the Colaizzi method, comprising seven distinct stages, facilitated by MAXQDA. Results: The analysis of the data resulted in the identification of 7 main themes and 46 sub-themes. These main themes encompass crucial aspects of the post-divorce parenting experience, namely: children's difficulties in adapting after divorce, parental psychological challenges, inter-parental conflicts, parental challenges in relating to their children, parental unfamiliarity with post-divorce parenting, and alterations in family structure following divorce, and the adoption of maladaptive parenting strategies by parents. Conclusion: Parents acknowledge that parenting after divorce poses significant challenges. The inter-parental relationship, the psychological well-being of parents post-divorce, their familiarity with effective parenting techniques, and the utilization of efficient parenting approaches in the context of changing family dynamics can profoundly influence children's adaptation to new circumstances.